(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The paper is focused on the research on virtual reality solutions which could be used to improve educational experience focusing on IT students. Current state of the art in the field of VR use for educational purposes was analysed. Pros and cons for VR implementation in education were considered. As the solution to enhance educational experience was proposed to integrate VR environment with learning management system in order to automate assessment for mass-learning courses. An example of such integration, a system based on Unity engine for VR laboratory environment development, and Moodle for learning management system, was presented. Experimental results obtained during testing of developed system proved possibility of proposed integration approach and possible benefits from its practical implementation for mass learning courses.